Ten grassland and arable soils show variable microbial responses to realistic pesticide mixtures - Laura Å. Medici; Antonia Lüthi; Pascal A. Niklaus; Marcel van der Heijden; Florian Walder; Miriam Langer (Applied Soil Ecology, 2026)

Seasonality of microbial functional potentials and community diversity in high-Arctic tundra soils - Aline Frossard; Ekaterina Pushkareva; Vivien Hotter; Pascal A. Niklaus; Bjorn Tytgat; David Velazquez; Madgalene Adamczyk; Beat Stierli; Antonio Quesada; Mette M. Svenning; Ulf Karsten; Elie Verleyen; et al. (Soil Biology and Biochemistry, 2026)

Impact of plant protection product applications on soil microbial nitrogen cycle function not fully captured by gene quantification - Laura Å. Medici; Pascal A. Niklaus; Florian Walder; Miriam Langer (Applied Soil Ecology, 2025)

Tree Diversity Increases Forest Temperature Buffering via Enhancing Canopy Density and Structural Diversity - Florian Schnabel; Rémy Beugnon; Bo Yang; Ronny Richter; Nico Eisenhauer; Yuanyuan Huang; Xiaojuan Liu; Christian Wirth; Simone Cesarz; Andreas Fichtner; Maria D. Perles‐Garcia; Georg J. A. Hähn; et al. (Ecology Letters, 2025)
Global warming is increasing the frequency and intensity of climate extremes. Forests may buffer climate extremes by creating their own attenuated microclimate below their canopy, which maintains forest functioning and biodiversity. However, the effect of tree diversity on temperature buffering in forests is largely unexplored. Here, we show that tree species richness increases forest temperature buffering across temporal scales over six years in a large‐scale tree diversity experiment covering a species richness gradient of 1 to 24 tree species. We found that species richness strengthened the cooling of hot and the insulation against cold daily and monthly air temperatures and temperature extremes. This buffering effect of tree species richness was mediated by enhanced canopy density and structural diversity in species‐rich stands. Safeguarding and planting diverse forests may thus mitigate negative effects of global warming and climate extremes on below‐canopy ecosystem functions and communities.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Biodiversity consequences of long-term active forest restoration in selectively-logged tropical rainforests - Nadine Keller; Pascal A. Niklaus; Jaboury Ghazoul; Tobias Marfil; Elia Godoong; Christopher D. Philipson (Forest Ecology and Management, 2023)

Experimental erosion of microbial diversity decreases soil CH 4 consumption rates - Elvira Schnyder; Paul L. E. Bodelier; Martin Hartmann; Ruth Henneberger; Pascal A. Niklaus (Ecology, 2023)
Biodiversity‐ecosystem functioning (BEF) experiments have predominantly focused on communities of higher organisms, in particular plants, with comparably little known to date about the relevance of biodiversity for microbially driven biogeochemical processes. Methanotrophic bacteria play a key role in Earth's methane (CH 4 ) cycle by removing atmospheric CH 4 and reducing emissions from methanogenesis in wetlands and landfills. Here, we used a dilution‐to‐extinction approach to simulate diversity loss in a methanotrophic landfill cover soil community. Replicate samples were diluted 10 1 –10 7 ‐fold, preincubated under a high CH 4 atmosphere for microbial communities to recover to comparable size, and then incubated for 86 days at constant or diurnally cycling temperature. We hypothesize that (1) CH 4 consumption decreases as methanotrophic diversity is lost, and (2) this effect is more pronounced under variable temperatures. Net CH 4 consumption was determined by gas chromatography. Microbial community composition was determined by DNA extraction and sequencing of amplicons specific to methanotrophs and bacteria ( pmoA and 16S gene fragments). The richness of operational taxonomic units (OTU) of methanotrophic and nonmethanotrophic bacteria decreased approximately linearly with log ‐dilution. CH 4 consumption decreased with the number of OTUs lost, independent of community size. These effects were independent of temperature cycling. The diversity effects we found occured in relatively diverse communities, challenging the notion of high functional redundancy mediating high resistance to diversity erosion in natural microbial systems. The effects also resemble the ones for higher organisms, suggesting that BEF relationships are universal across taxa and spatial scales.

Do temporal and spatial heterogeneity modulate biodiversity–functioning relationships in com-munities of methanotrophic bacteria? - Elvira Schnyder; Paul L.E. Bodelier; Martin Hartmann; Ruth Henneberger; Pascal A. Niklaus (Soil Biology and Biochemistry, 2023)

Precipitation patterns and N availability legacy govern microbial response to rewetting in a plant-soil system - Ilonka C. Engelhardt; Pascal A. Niklaus; Florian Bizouard; David Bru; Marie-Christine Breuil; Nadine Rouard; Arnaud Mounier; Laurent Philippot; Romain L. Barnard (Soil Biology and Biochemistry, 2023)

A spatial fingerprint of land-water linkage of biodiversity uncovered by remote sensing and environmental DNA - Heng Zhang; Elvira Mächler; Felix Morsdorf; Pascal A. Niklaus; Michael E. Schaepman; Florian Altermatt (Science of The Total Environment, 2023)

Soil Fungi Promote Biodiversity–Productivity Relationships in Experimental Communities of Young Trees - Bo Yang; Yu Liang; Bernhard Schmid; Martin Baruffol; Yangfan Li; Ling He; Yann Salmon; Qiuyang Tian; Pascal A. Niklaus; Keping Ma (Ecosystems, 2022)

Precipitation patterns and N availability alter plant-soil microbial C and N dynamics - Ilonka C. Engelhardt; Pascal A. Niklaus; Florian Bizouard; Marie-Christine Breuil; Nadine Rouard; Florence Deau; Laurent Philippot; Romain L. Barnard (Plant and Soil, 2021)

Tree-species interactions increase light absorption and growth in Chinese subtropical mixed-species plantations - David I. Forrester; Peter Rodenfels; Josephine Haase; Werner Härdtle; Katrin N. Leppert; Pascal A. Niklaus; Goddert von Oheimb; Michael Scherer-Lorenzen; Jürgen Bauhus (Oecologia, 2019)

Positive diversity‐functioning relationships in model communities of methanotrophic bacteria - Elvira Schnyder; Paul L. E. Bodelier; Martin Hartmann; Ruth Henneberger; Pascal A. Niklaus (Ecology, 2018)
Biodiversity enhances ecosystem functions such as biomass production and nutrient cycling. Although the majority of the terrestrial biodiversity is hidden in soils, very little is known about the importance of the diversity of microbial communities for soil functioning. Here, we tested effects of biodiversity on the functioning of methanotrophs, a specialized group of soil bacteria that plays a key role in mediating greenhouse gas emissions from soils. Using pure strains of methanotrophic bacteria, we assembled artificial communities of different diversity levels, with which we inoculated sterile soil microcosms. To assess the functioning of these communities, we measured methane oxidation by gas chromatography throughout the experiment and determined changes in community composition and community size at several time points by quantitative PCR and sequencing. We demonstrate that microbial diversity had a positive overyielding effect on methane oxidation, in particular at the beginning of the experiment. This higher assimilation of CH 4 at high diversity translated into increased growth and significantly larger communities towards the end of the study. The overyielding of mixtures with respect to CH 4 consumption and community size were positively correlated. The temporal CH 4 consumption profiles of strain monocultures differed, raising the possibility that temporal complementarity of component strains drove the observed community‐level strain richness effects; however, the community niche metric we derived from the temporal activity profiles did not explain the observed strain richness effect. The strain richness effect also was unrelated to both the phylogenetic and functional trait diversity of mixed communities. Overall, our results suggest that positive biodiversity–ecosystem‐function relationships show similar patterns across different scales and may be widespread in nature. Additionally, biodiversity is probably also important in natural methanotrophic communities for the ecosystem function methane oxidation. Therefore, maintaining soil conditions that support a high diversity of methanotrophs may help to reduce the emission of the greenhouse gas methane.

Reconstruction of Historic Forest Cover Changes Indicates Minor Effects on Carbon Stocks in Swiss Forest Soils - Sia Gosheva; Lorenz Walthert; Pascal A. Niklaus; Stephan Zimmermann; Urs Gimmi; Frank Hagedorn (Ecosystems, 2017)

Leaf litter diversity positively affects the decomposition of plant polyphenols - Christian Ristok; Katrin N. Leppert; Katrin Franke; Michael Scherer-Lorenzen; Pascal A. Niklaus; Ludger A. Wessjohann; Helge Bruelheide (Plant and Soil, 2017)

Spatial micro-distribution of methanotrophic activity along a 120-year afforestation chronosequence - Saeed Karbin; Frank Hagedorn; David Hiltbrunner; Stefan Zimmermann; Pascal A. Niklaus (Plant and Soil, 2017)

Can niche plasticity promote biodiversity–productivity relationships through increased complementarity? - Pascal A. Niklaus; Martin Baruffol; Jin‐Sheng He; Keping Ma; Bernhard Schmid (Ecology, 2017)
Most experimental biodiversity–ecosystem functioning research to date has addressed herbaceous plant communities. Comparably little is known about how forest communities will respond to species losses, despite their importance for global biogeochemical cycling. We studied tree species interactions in experimental subtropical tree communities with 33 distinct tree species mixtures and one, two, or four species. Plots were either exposed to natural light levels or shaded. Trees grew rapidly and were intensely competing above ground after 1.5 growing seasons when plots were thinned and the vertical distribution of leaves and wood determined by separating the biomass of harvested trees into 50 cm height increments. Our aim was to analyze effects of species richness in relation to the vertical allocation of leaf biomass and wood, with an emphasis on bipartite competitive interactions among species. Aboveground productivity increased with species richness. The community‐level vertical leaf and wood distribution depended on the species composition of communities. Mean height and breadth of species‐level vertical leaf and wood distributions did not change with species richness. However, the extra biomass produced by mixtures compared to monocultures of the component species increased when vertical leaf distributions of monocultures were more different. Decomposition of biodiversity effects with the additive partitioning scheme indicated positive complementarity effects that were higher in light than in shade. Selection effects did not deviate from zero, irrespective of light levels. Vertical leaf distributions shifted apart in mixed stands as consequence of competition‐driven phenotypic plasticity, promoting realized complementarity. Structural equation models showed that this effect was larger for species that differed more in growth strategies that were characterized by functional traits. In 13 of the 18 investigated two‐species mixtures, both species benefitted relative to intraspecific competition in monoculture. In the remaining five pairwise mixtures, the relative yield gain of one species exceeded the relative yield loss of the other species, resulting in a relative yield total ( RYT ) exceeding 1. Overall, our analysis indicates that richness–productivity relationships are promoted by interspecific niche complementarity at early stages of stand development, and that this effect is enhanced by architectural plasticity.

Plant species diversity affects soil–atmosphere fluxes of methane and nitrous oxide - Pascal A. Niklaus; Xavier Le Roux; Franck Poly; Nina Buchmann; Michael Scherer-Lorenzen; Alexandra Weigelt; Romain L. Barnard (Oecologia, 2016)

Options of partners improve carbon for phosphorus trade in the arbuscular mycorrhizal mutualism - Alicia Argüello; Michael J. O'Brien; Marcel G.A. van der Heijden; Andres Wiemken; Bernhard Schmid; Pascal A. Niklaus (Ecology Letters, 2016)
The mutualism between plants and arbuscular mycorrhizal fungi ( AMF ) is widespread and has persisted for over 400 million years. Although this mutualism depends on fair resource exchange between plants and fungi, inequality exists among partners despite mechanisms that regulate trade. Here, we use 33 P and 14 C isotopes and a split‐root system to test for preferential allocation and reciprocal rewards in the plant– AMF symbiosis by presenting a plant with two AMF that differ in cooperativeness. We found that plants received more 33 P from less cooperative AMF in the presence of another AMF species. This increase in 33 P resulted in a reduced 14 C cost per unit of 33 P from less cooperative AMF when alternative options were available. Our results indicate that AMF diversity promotes cooperation between plants and AMF , which may be an important mechanism maintaining the evolutionary persistence of and diversity within the plant– AMF mutualism.

Plant diversity drives soil microbial biomass carbon in grasslands irrespective of global environmental change factors - Madhav Prakash Thakur; Alexandru Milcu; Pete Manning; Pascal A. Niklaus; Christiane Roscher; Sally Power; Peter B. Reich; Stefan Scheu; David Tilman; Fuxun Ai; Hongyan Guo; Rong Ji; et al. (Global Change Biology, 2015)
Soil microbial biomass is a key determinant of carbon dynamics in the soil. Several studies have shown that soil microbial biomass significantly increases with plant species diversity, but it remains unclear whether plant species diversity can also stabilize soil microbial biomass in a changing environment. This question is particularly relevant as many global environmental change ( GEC ) factors, such as drought and nutrient enrichment, have been shown to reduce soil microbial biomass. Experiments with orthogonal manipulations of plant diversity and GEC factors can provide insights whether plant diversity can attenuate such detrimental effects on soil microbial biomass. Here, we present the analysis of 12 different studies with 14 unique orthogonal plant diversity × GEC manipulations in grasslands, where plant diversity and at least one GEC factor (elevated CO 2 , nutrient enrichment, drought, earthworm presence, or warming) were manipulated. Our results show that higher plant diversity significantly enhances soil microbial biomass with the strongest effects in long‐term field experiments. In contrast, GEC factors had inconsistent effects with only drought having a significant negative effect. Importantly, we report consistent non‐significant effects for all 14 interactions between plant diversity and GEC factors, which indicates a limited potential of plant diversity to attenuate the effects of GEC factors on soil microbial biomass. We highlight that plant diversity is a major determinant of soil microbial biomass in experimental grasslands that can influence soil carbon dynamics irrespective of GEC .

A comparison of the strength of biodiversity effects across multiple functions - Eric Allan; Wolfgang W. Weisser; Markus Fischer; Ernst-Detlef Schulze; Alexandra Weigelt; Christiane Roscher; Jussi Baade; Romain L. Barnard; Holger Beßler; Nina Buchmann; Anne Ebeling; Nico Eisenhauer; et al. (Oecologia, 2013)

Erratum to: Effects of drought and N-fertilization on N cycling in two grassland soils - Adrian A. Hartmann; Romain L. Barnard; Sven Marhan; Pascal A. Niklaus (Oecologia, 2013)

Effects of drought and N-fertilization on N cycling in two grassland soils - Adrian A. Hartmann; Romain L. Barnard; Sven Marhan; Pascal A. Niklaus (Oecologia, 2013)

Effects of simulated drought and nitrogen fertilizer on plant productivity and nitrous oxide (N2O) emissions of two pastures - Adrian A. Hartmann; Pascal A. Niklaus (Plant and Soil, 2012)

Forest soil respiration reflects plant productivity across a temperature gradient in the Alps - Riccarda Caprez; Pascal A. Niklaus; Christian Körner (Oecologia, 2012)

Increasing soil methane sink along a 120‐year afforestation chronosequence is driven by soil moisture - David Hiltbrunner; Stephan Zimmermann; Saeed Karbin; Frank Hagedorn; Pascal A. Niklaus (Global Change Biology, 2012)
Upland soils are important sinks for atmospheric methane ( CH 4 ), a process essentially driven by methanotrophic bacteria. Soil CH 4 uptake often depends on land use, with afforestation generally increasing the soil CH 4 sink. However, the mechanisms driving these changes are not well understood to date. We measured soil CH 4 and N 2 O fluxes along an afforestation chronosequence with Norway spruce (Picea abies L.) established on an extensively grazed subalpine pasture. Our experimental design included forest stands with ages ranging from 25 to >120 years and included a factorial cattle urine addition treatment to test for the sensitivity of soil CH 4 uptake to N application. Mean CH 4 uptake significantly increased with stand age on all sampling dates. In contrast, CH 4 oxidation by sieved soils incubated in the laboratory did not show a similar age dependency. Soil CH 4 uptake was unrelated to soil N status (but cattle urine additions stimulated N 2 O emission). Our data indicated that soil CH 4 uptake in older forest stands was driven by reduced soil water content, which resulted in a facilitated diffusion of atmospheric CH 4 into soils. The lower soil moisture likely resulted from increased interception and/or evapotranspiration in the older forest stands. This mechanism contrasts alternative explanations focusing on nitrogen dynamics or the composition of methanotrophic communities, although these factors also might be at play. Our findings further imply that the current dramatic increase in forested area increases CH 4 uptake in alpine regions.

Do grassland plant communities profit from N partitioning by soil depth? - Stefanie von Felten; Pascal A. Niklaus; Michael Scherer-Lorenzen; Andrew Hector; Nina Buchmann (Ecology, 2012)
Recent biodiversity–ecosystem functioning experiments in temperate grasslands have shown that productivity positively correlates with plant species richness. Resource partitioning (in particular, nitrogen [N] partitioning) has been proposed as one possible mechanism to explain this pattern. There is evidence for interspecific differences in chemical form, soil depth, and timing of N uptake. However, it has rarely been tested whether such differences result in increased N exploitation at the plant community level. Using 15 N‐labeled litter that was mixed into different soil layers, we tested whether eight common grasses and forbs grown in communities of one, two, or four species differ with respect to the proportions of N taken up from different soil depths (N niche), and how this affects the total N uptake of plant communities. We calculated proportional similarity between species (niche overlap) with regard to N uptake from the labeled soil layers; we further calculated an a priori measure of community N uptake based on species N uptake in monoculture (community niche). Interestingly, however, plant community N uptake was not affected by species richness, possibly because community‐level N uptake was determined by (diversity‐independent) soil N mineralization rates. We nevertheless observed a positive effect of species richness on productivity due to increased aboveground biomass : N ratios. This may indicate increased competition for light, resulting in increased amounts of comparably N‐poor stem tissue. However, community N content and biomass were positively correlated with the community niche, a measure which is strongly linked to species composition. Thus, our results suggest that the studied species are generalists rather than specialists regarding N uptake depth, and that species composition was more important than species richness in determining community N uptake. Overall, N partitioning may be a less important driver of positive biodiversity–productivity effects in temperate grasslands than previously assumed.

A study of soil methane sink regulation in two grasslands exposed to drought and N fertilization - Adrian A. Hartmann; Nina Buchmann; Pascal A. Niklaus (Plant and Soil, 2011)

A meta-analysis of responses of soil biota to global change - Joseph C. Blankinship; Pascal A. Niklaus; Bruce A. Hungate (Oecologia, 2011)

Indirect effects of soil moisture reverse soil C sequestration responses of a spring wheat agroecosystem to elevated CO 2 - SVEN MARHAN; ELLEN KANDELER; STEFANIE REIN; ANDREAS FANGMEIER; PASCAL A. NIKLAUS (Global Change Biology, 2010)
Increased plant productivity under elevated atmospheric CO 2 concentrations might increase soil carbon (C) inputs and storage, which would constitute an important negative feedback on the ongoing atmospheric CO 2 rise. However, elevated CO 2 often also leads to increased soil moisture, which could accelerate the decomposition of soil organic matter, thus counteracting the positive effects via C cycling. We investigated soil C sequestration responses to 5 years of elevated CO 2 treatment in a temperate spring wheat agroecosystem. The application of 13 C‐depleted CO 2 to the elevated CO 2 plots enabled us to partition soil C into recently fixed C (C new ) and pre‐experimental C (C old ) by 13 C/ 12 C mass balance. Gross C inputs to soils associated with C new accumulation and the decomposition of C old were then simulated using the Rothamsted C model ‘RothC.’ We also ran simulations with a modified RothC version that was driven directly by measured soil moisture and temperature data instead of the original water balance equation that required potential evaporation and precipitation as input. The model accurately reproduced the measured C new in bulk soil and microbial biomass C. Assuming equal soil moisture in both ambient and elevated CO 2 , simulation results indicated that elevated CO 2 soils accumulated an extra ∼40–50 g C m −2 relative to ambient CO 2 soils over the 5 year treatment period. However, when accounting for the increased soil moisture under elevated CO 2 that we observed, a faster decomposition of C old resulted; this extra C loss under elevated CO 2 resulted in a negative net effect on total soil C of ∼30 g C m −2 relative to ambient conditions. The present study therefore demonstrates that positive effects of elevated CO 2 on soil C due to extra soil C inputs can be more than compensated by negative effects of elevated CO 2 via the hydrological cycle.

Belowground nitrogen partitioning in experimental grassland plant communities of varying species richness - Stefanie von Felten; Andrew Hector; Nina Buchmann; Pascal A. Niklaus; Bernhard Schmid; Michael Scherer-Lorenzen (Ecology, 2009)
Partitioning of soil nitrogen (N) by niche separation among species may be an important mechanism explaining species coexistence and positive biodiversity–productivity relationships in terrestrial plant communities. However, there is little experimental evidence for such partitioning, in particular, as assessed across a gradient of species richness. In experimental communities of one, three, and six temperate grassland species in the field, we tested whether increasing species richness (1) decreases niche breadths of individual species, (2) decreases niche overlap among species, and (3) increases niche breadth of whole communities. Six N sources consisting of three different chemical forms of 15 N‐labeled N ( 15 NO 3 − , 15 NH 4 + , 13 C 2 ‐ 15 N‐glycine) injected at two soil depths (3 and 12 cm) were applied to each community. The chemical form and the soil depth of N characterize the niches for which niche breadth (Levins' B ) and overlap (proportional similarity) were measured. After 48 hours, aboveground plant material was harvested to measure 15 N enrichment. As expected, niche breadth of single species and niche overlap among species decreased with increased species richness, but community niche breadth did not increase. The decrease in niche breadth and niche overlap mostly occurred among subordinate species or pairs of subordinate and dominant species, rather than among dominant species. Species in the six‐species mixtures mostly preferred NO 3 − from shallow soil. This may be partly explained by the presence of legumes in all six‐species mixtures which allowed “N sparing” (i.e., increased availability of soil N since legumes rely more on atmospheric N 2 than on soil N). Niche separation with respect to N uptake from different chemical forms and soil depths did not contribute much to facilitating the coexistence of dominant species, nor do our results suggest it as a major driver of positive diversity–ecosystem functioning relationships. However, partitioning of N may be important for the persistence of subordinate species.

Estimating soil carbon sequestration under elevated CO 2 by combining carbon isotope labelling with soil carbon cycle modelling - PASCAL A. NIKLAUS; PETE FALLOON (Global Change Biology, 2006)
Elevated CO 2 concentrations generally stimulate grassland productivity, but herbaceous plants have only a limited capacity to sequester extra carbon (C) in biomass. However, increased primary productivity under elevated CO 2 could result in increased transfer of C into soils where it could be stored for prolonged periods and exercise a negative feedback on the rise in atmospheric CO 2 . Measuring soil C sequestration directly is notoriously difficult for a number of methodological reasons. Here, we present a method that combines C isotope labelling with soil C cycle modelling to partition net soil sequestration into changes in new C fixed over the experimental duration (C new ) and pre‐experimental C (C old ). This partitioning is advantageous because the C new accumulates whereas C old is lost in the course of time (ΔC new >0 whereas ΔC old We applied this method to calcareous grassland exposed to 600 μL CO 2 L −1 for 6 years. The CO 2 used for atmospheric enrichment was depleted in 13 C relative to the background atmosphere, and this distinct isotopic signature was used to quantify net soil C new fluxes under elevated CO 2 . Using 13 C/ 12 C mass balance and inverse modelling, the Rothamsted model ‘RothC’ predicted gross soil C new inputs under elevated CO 2 and the decomposition of C old . The modelled soil C pools and fluxes were in good agreement with experimental data. C isotope data indicated a net sequestration of ≈90 g C new m −2 yr −1 in elevated CO 2 . Accounting for C old ‐losses, this figure was reduced to ≈30 g C m −2 yr −1 at elevated CO 2 ; the elevated CO 2 ‐effect on net C sequestration was in the range of≈10 g C m −2 yr −1 . A sensitivity and error analysis suggests that the modelled data are relatively robust. However, elevated CO 2 ‐specific mechanisms may necessitate a separate parameterization at ambient and elevated CO 2 ; these include increased soil moisture due to reduced leaf conductance, soil disaggregation as a consequence of increased soil moisture, and priming effects. These effects could accelerate decomposition of C old in elevated CO 2 so that the CO 2 enrichment effect may be zero or even negative. Overall, our findings suggest that the C sequestration potential of this grassland under elevated CO 2 is rather limited.

Effects of Plant Species Diversity and Composition on Nitrogen Cycling and the Trace Gas Balance of Soils - Pascal A. Niklaus; David A. Wardle; Kevin R. Tate (Plant and Soil, 2006)

Effects of long term CO2 enrichment on microbial community structure in calcareous grassland - Diana Ebersberger; Nicola Wermbter; Pascal A. Niklaus; Ellen Kandeler (Plant and Soil, 2004)

Effects of six years atmospheric CO2 enrichment on plant, soil, and soil microbial C of a calcareous grassland - Pascal A. Niklaus; Monika Wohlfender; Rolf Siegwolf; Christian Körner (Plant and Soil, 2001)

A link between plant diversity, elevated CO2 and soil nitrate - Pascal A. Niklaus; E. Kandeler; P.W. Leadley; B. Schmid; D. Tscherko; C. Körner (Oecologia, 2001)

Soil moisture effects determine CO2 responses of grassland species - Matthias Volk; Pascal A. Niklaus; Christian Körner (Oecologia, 2000)

A field study of the effects of elevated CO 2 on plant biomass and community structure in a calcareous grassland - Paul W. Leadley; Pascal A. Niklaus; Reto Stocker; Christian Körner (Oecologia, 1999)

Soil moisture dynamics of calcareous grassland under elevated CO 2 - Pascal A. Niklaus; D. Spinnler; C. Körner (Oecologia, 1998)

Nutrient relations in calcareous grassland under elevated CO 2 - Pascal A. Niklaus; Paul W. Leadley; Jrg Stcklin; Christian Krner (Oecologia, 1998)

Effects of elevated atmospheric CO 2 on soil microbiota in calcareous grassland - Pascal A. Niklaus (Global Change Biology, 1998)
Microbial responses to three years of CO 2 enrichment (600 μL L –1 ) in the field were investigated in calcareous grassland. Microbial biomass carbon (C) and soil organic C and nitrogen (N) were not significantly influenced by elevated CO 2 . Microbial C:N ratios significantly decreased under elevated CO 2 (– 15%, P = 0.01) and microbial N increased by + 18% ( P = 0.04). Soil basal respiration was significantly increased on one out of 7 sampling dates (+ 14%, P = 0.03; December of the third year of treatment), whereas the metabolic quotient for CO 2 (qCO 2 = basal respiration/microbial C) did not exhibit any significant differences between CO 2 treatments. Also no responses of microbial activity and biomass were found in a complementary greenhouse study where intact grassland turfs taken from the field site were factorially treated with elevated CO 2 and phosphorus (P) fertilizer (1 g P m –2 y –1 ). Previously reported C balance calculations showed that in the ecosystem investigated growing season soil C inputs were strongly enhanced under elevated CO 2 . It is hypothesized that the absence of microbial responses to these enhanced soil C fluxes originated from mineral nutrient limitations of microbial processes. Laboratory incubations showed that short‐term microbial growth (one week) was strongly limited by N availability, whereas P was not limiting in this soil. The absence of large effects of elevated CO 2 on microbial activity or biomass in such nutrient‐poor natural ecosystems is in marked contrast to previously published large and short‐term microbial responses to CO 2 enrichment which were found in fertilized or disturbed systems. It is speculated that the absence of such responses in undisturbed natural ecosystems in which mineral nutrient cycles have equilibrated over longer periods of time is caused by mineral nutrient limitations which are ineffective in disturbed or fertilized systems and that therefore microbial responses to elevated CO 2 must be studied in natural, undisturbed systems.